Clinical practice guideline on the management of septic shock and sepsis‐associated organ dysfunction in children: Endorsement by the Scandinavian Society of Anaesthesiology and Intensive Care Medicine. Issue 10 (4th August 2021) - Rehn, Marius; Chew, Michelle S.; Olkkola, Klaus T.; Sigurðsson, Martin Ingi; Yli‐Hankala, Arvi; Møller, Morten Hylander
Abstract: Background: The Clinical Practice Committee of the Scandinavian Society of Anaesthesiology and Intensive Care Medicine endorses the clinical practice guideline Surviving Sepsis Campaign International Guidelines for the Management of Septic Shock and Sepsis ‐ Associated Organ Dysfunction in Children . The guideline can serve as a useful decision aid for clinicians managing children with suspected and confirmed septic shock and sepsis‐associated organ dysfunction.